FAKTOR PENYEBAB TURUNNYA PARTISIPASI PEMILIH PADA PILKADA KABUPATEN SUMBAWA 2024 : (STUDI PADA STRATEGI KOMISI PEMILIHAN UMUM KABUPATEN SUMBAWA) - Lasmi Indah Sari; Leni Nurul Kariyani (Yayasan Nusantara Hasana Berdikari, 2026)
Community political participation is an important indicator in assessing the quality of local democracy, particularly in the implementation of regional head elections (pilkada). In the 2024 sumbawa regency pilkada, the level of voter participation showed a declining trend compared to the previous period, indicating the need for an in-depth study of the election organizer’s strategy. This study aims to analyze the factors causing the decline in voter participation in the 2024 sumbawa regency pilkada (a study on the strategy of the sumbawa regency general election commission). Specifically, this research examines the factors contributing to the decrease in voter participation and analyzes the strategy of the general election commission (komisi pemilihan umum/kpu) of sumbawa regency in the implementation of the 2024 pilkada. The focus of the study is directed toward the kpu’s program strategy in the form of voter education and socialization activities and their relation to voter participation levels. This research employs a qualitative method with a descriptive approach. Data were collected through interviews, observation, and documentation involving informants from the kpu of sumbawa regency and members of the community. The data were analyzed through the stages of data reduction, data presentation, and conclusion drawing. The findings indicate that the kpu of sumbawa regency has implemented program strategies through public meetings, social action activities, and the provision of complaint channels as a means of public participation. However, the implementation of these strategies still faces limitations in terms of outreach, the predominance of face-to-face socialization methods, and the socio-economic conditions of the community that affect voter engagement. In conclusion, the limited effectiveness of the kpu’s program strategy is one of the factors contributing to the decline in voter participation in the 2024 sumbawa regency regional head election.